Bone Recontouring by Guided Surgical Navigation Integrating “Mirroring” Computational Planning in the Management of Severe Fronto-orbital Asymmetry in Fibrous Dysplasia - Guatta, Ramona; Scolozzi, Paolo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
We report the successful treatment of severe fronto-orbital asymmetry in a 20-year-old man with fibrous dysplasia by bone recontouring using a specific approach combining “mirroring” virtual computational planning with intraoperative guided surgical navigation.
Keywords: computer-assisted surgery; navigation system; fibrous dysplasia